Influence of tool geometry and process parameters on macrostructure and static strength in friction stir spot welded polyethylene sheets - BİLİCİ, MUSTAFA KEMAL (My University, 2012)
The effect of important welding parameters and tool properties that are effective on static strength in friction stir spot welds of polyethylene sheets were studied. Six different tool pin profiles (straight cylindrical, tapered cylindrical, threaded cylindrical, triangular, square and hexagonal) with different shoulder geometries, different pin length, pin angle and concavity angle were used to fabricate the joints. The tool rotational speed, tool plunge depth and dwell time were determined welding parameters. All the welding operations were done at the room temperature. Welding force and welding zone material temperature measurements were also done. Lap-shear tests were carried out to find the weld static strength. Weld cross section appearance observations were also done. From the experiments, the effect of pin profile, pin length, pin angle, dwell time and tool rotational speed on friction stir spot welding formation and weld strength was determined. © 2011 Elsevier Ltd.